1997
DOI: 10.1016/s0001-2092(06)62999-2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Music During the Immediate Postoperative Recovery Period

Abstract: The most effective approach to managing patients' pain in the immediate postoperative period may include a combination of pharmacologic agents and noninvasive, nonpharmacologic interventions. In this study, nurse researchers evaluated the effect of music on pain and anxiety levels and selected physiologic parameters of two groups of patients who were emerging and recovering from anesthesia. Patients in the treatment group listened to music through head-phones during the last 30 minutes of their surgical proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 12 publications
5
43
0
2
Order By: Relevance
“…Group sizes of Ͼ100 (Table 1) were probably the reason the findings were more positive than those in small preliminary studies. Several investigators found the interventions reduced only the affective component of pain at rest (Mogan et al, 1985;n = 40;Wells, 1982;n = 6;Wilson, 1981; n = 18) or music reduced different pain components on different days (Good and Chin, 1998; n = 16), or had no significant results for relaxation (Voshall, 1980; n = 15); or for music in the recovery room (Heitz et al, 1992; n = 20) (Heiser et al, 1997; n = 5) or following cardiac surgery (Zimmerman et al, 1996; n = 26). In future studies, relationships between duration of use, relief and occurrence of side effects and complications should be explored, along with effects of relief on stress and immune responses.…”
Section: Restmentioning
confidence: 99%
See 1 more Smart Citation
“…Group sizes of Ͼ100 (Table 1) were probably the reason the findings were more positive than those in small preliminary studies. Several investigators found the interventions reduced only the affective component of pain at rest (Mogan et al, 1985;n = 40;Wells, 1982;n = 6;Wilson, 1981; n = 18) or music reduced different pain components on different days (Good and Chin, 1998; n = 16), or had no significant results for relaxation (Voshall, 1980; n = 15); or for music in the recovery room (Heitz et al, 1992; n = 20) (Heiser et al, 1997; n = 5) or following cardiac surgery (Zimmerman et al, 1996; n = 26). In future studies, relationships between duration of use, relief and occurrence of side effects and complications should be explored, along with effects of relief on stress and immune responses.…”
Section: Restmentioning
confidence: 99%
“…In some studies relaxation or music reduced reports of sensory and affective pain (Flaherty and Fitzpatrick, 1978;Lawlis et al, 1985;Levin et al, 1987;Mullooly et al, 1988;Miller and Perry, 1990), while in others they reduced only affective pain (Wells, 1982;Horowitz et al, 1984;Mogan et al, 1985), had different results on different measures of pain (Good and Chin, 1998), or on different postoperative days (Good, 1995;Good and Chin, 1998). In other studies relaxation or music had no effect on pain but reportedly, provided a relaxing and pleasant experience (Heitz et al, 1992;Zimmerman et al, 1996;Heiser et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to minimize the anxiety symptoms of children undergoing surgery and familiarize them with the procedures to enhance their coping skills, healthcare professionals have developed preoperative preparation programs (O'Byrne, Peterson, & Saldana, 1997;Rice, Glasper, Keeton, & Spargo, 2008) and investigated the benefits of some interventions, such as the presence of a family member during the induction of anesthesia (McCann & Kain, 2001;Shirley, et al, 1998;Wollin, Plummer, Owen, Hawkins, & Materazzo, 2003), educational videos (Cassady, Wysocki, Miller, Cancel, & Izenberg, 1999), books (Felder-Puig, et al, 2003), and the use of several distracters such as music (Augustin & Hains, 1996;Heiser, Chiles, Fudge, & Gray, 1997;Kain, et al, 2004), video games (Patel, et al, 2006), and toys (Golden, et al, 2006). Based on the assumption that humor is associated with the well-being of patients (Bennett & Lengacher, 2006a, 2006bMartin, 2001;Stuber, et al, 2007), there has been an increase in interventions provided by "clown doctors" in pediatric settings (Koller & Gryski, 2008).…”
mentioning
confidence: 99%
“…Some studies have failed to show a significant difference in reduction of pain with music (Broscious, 1999;Good, 1995 andHeiser et al, 1997). Some studies have not demonstrated reduction in anxiety levels with music therapy (Good, 1995;Heiser et al, 1997 andKwekkeboom, 2003).…”
Section: Limitations / Drawbacks Of Musicmentioning
confidence: 99%
“…Some studies have not demonstrated reduction in anxiety levels with music therapy (Good, 1995;Heiser et al, 1997 andKwekkeboom, 2003). Some types of music like rock music can elevate the blood pressure (Crippa et al, 2012).…”
Section: Limitations / Drawbacks Of Musicmentioning
confidence: 99%